2022
DOI: 10.1155/2022/2762067
|View full text |Cite|
|
Sign up to set email alerts
|

Approach to Multiattribute Decision-Making Problems Based on Neutrality Aggregation Operators of Picture Fuzzy Information

Abstract: This manuscript is aimed at developing some novel operational laws named scalar neutrality operation and neutrality addition on picture fuzzy numbers (PFNs). The main focus of this work is to involve the neutral behaviour of the experts towards the priorities of entities where it presents equal degrees to independent membership functions. Moreover, based on these operations, some novel aggregation operators are established to aggregate the different priorities of experts. Some useful relations and characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…In the future, our goal would be to review various notions like the bipolar complex fuzzy soft set (SS) (Mahmood et al, 2022c), Pythagorean FS (Li et al, 2022), picture FS (Ullah, 2021), picture fuzzy SSs (Khan et al, 2019), T-spherical FS (Javed et al, 2022), complex bipolar intuitionistic FS (Jan et al, 2022), enhancing digital innovation for the sustainable transformation of manufacturing industry (Yin et al, 2022) and try to employ the introduced work in these notions.…”
Section: Discussionmentioning
confidence: 99%
“…In the future, our goal would be to review various notions like the bipolar complex fuzzy soft set (SS) (Mahmood et al, 2022c), Pythagorean FS (Li et al, 2022), picture FS (Ullah, 2021), picture fuzzy SSs (Khan et al, 2019), T-spherical FS (Javed et al, 2022), complex bipolar intuitionistic FS (Jan et al, 2022), enhancing digital innovation for the sustainable transformation of manufacturing industry (Yin et al, 2022) and try to employ the introduced work in these notions.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that the AOs designed for different fuzzy structures fail to address issues expressed as SFNs. In order to assess the efficacy of our proposed method and make comparisons with other existing techniques cited in the literature [32], [40], [42], [45], [48]- [50], we perform a comprehensive analysis of validity and comparison utilizing NAOs. In this analysis, we utilize several other aggregating methods and ranking tools, such as the spherical fuzzy weighted averaging (SFWA) operator [27], spherical fuzzy weighted geometric (SFWG) operator [27], spherical fuzzy weighted Dombi averaging (SFWDA) operator [29], spherical fuzzy weighted Dombi geometric (SFWDG) operator [29].…”
Section: Verification and Comparative Analysismentioning
confidence: 99%
“…Further, Liu et al [37] developed the similarity measures for inter-valued picture fuzzy sets to solve decision-making problems. Javed et al [38] devised the novel neutrality aggregation operators which are very useful to solve the MCDM problems. In order to deal with such circumstances, we propose to introduce a new concept of picture fuzzy hypersoft matrices (PFHSM) which would certainly improve the enumerating power and variability of the available information.…”
Section: Renewable Energy Source Descriptions and Literature Reviewmentioning
confidence: 99%